2010
DOI: 10.1007/s12311-010-0230-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effects of Theta Burst Stimulation on Cerebellar Nonsomatic Functions

Abstract: Clinical and functional imaging studies suggest that the cerebellar vermis is involved in the regulation of a range of nonsomatic functions including cardiovascular control, thirst, feeding behavior, and primal emotions. Cerebello-hypothalamic circuits have been postulated to be a potential neuroanatomical substrate underlying this modulation. We tested this putative relationship between the cerebellar vermis and nonsomatic functions by stimulating the cerebellum noninvasively via neuronavigated transcranial m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 116 publications
1
39
0
Order By: Relevance
“…Regarding TMS, other targets have been implicated in the ANS modulation in humans, such as the spinal cord (Paxton et al, 2011) and cerebellum (Demirtas-Tatlidede et al, 2011). Therefore, these two regions (spinal cord and cerebellum) should be further explored in future studies addressing ANS modulation induced by NIBS.…”
Section: Parametersmentioning
confidence: 99%
“…Regarding TMS, other targets have been implicated in the ANS modulation in humans, such as the spinal cord (Paxton et al, 2011) and cerebellum (Demirtas-Tatlidede et al, 2011). Therefore, these two regions (spinal cord and cerebellum) should be further explored in future studies addressing ANS modulation induced by NIBS.…”
Section: Parametersmentioning
confidence: 99%
“…In this special issue, Jeremy Schmahmann and colleagues examine the putative function of cerebellarhypothalamic pathways using intermittent theta burst stimulation to modulate activity in experimentally targeted regions of the cerebellum [13]. Although clearly the resolution of zonal architecture is not as detailed as anatomical studies reveal, the authors present two important findings: (1) the cerebellum may modulate several non-somatic functions including cardiovascular control, thirst, and feeding and (2) the control of these functions appears to be regionally localized with a major influence coming from the posterior cerebellar vermis.…”
mentioning
confidence: 99%
“…By means of ectomy and lesion techniques, previous behavioral studies have revealed that the cerebellum is involved in diverse facets of feeding behavior, such as nutritional metabolism, taste preferences and body weight gain (Scalera 1991;Mahler et al 1993;Colombel et al 2002). Furthermore, evidence from clinical and functional imaging studies suggests that the cerebellum is closely related to hunger, satiation, thirst, glucose intake and appetite (Schmahmann et al 1999;Tataranni et al 1999;Liu et al 2000;Parsons et al 2000;Demirtas-Tatlidede et al 2011).…”
Section: Discussionmentioning
confidence: 99%